Use of Objective Outcomes Measures to Verify the Effects of ICF-Based Gait Treatment in Huntington's Disease Patient on Globus Pallidus Deep Brain Stimulation: A Case Report - Capato, Tamine T. C.; Cury, Rubens G.; Tornai, Juliana; Fonoff, Erich T.; Guimarães, Renata; Jacobsen, Manoel T.; Haddad, Mônica S.; Barbosa, Egberto R. (Frontiers in Rehabilitation Sciences, 2022)
In advanced stages of in Huntington's disease (HD) gait impairments and severe chorea are usually medication-refractory. The long-term effects on gait in HD of physiotherapy ICF-based management post- globus pallidus deep brain stimulation (GPi DBS) are not well established. Physiotherapy has been recognized as an essential element in HD treatment. Here, we present a case report of a 56-year-old woman with HD on the advanced stage and severe chorea medication-refractory after GPi-DBS. We performed multidisciplinary motor assessments ICF-based to identify the disability at clinical and home-setting, including environmental and personal factors before and after GPi-DBS surgery and at 11-time points follow-up. The surgery was very successful and directly post GPi-DBS, there were a significant improvement in chorea and a substantial decrease in medication dose. A framework ICF- based physiotherapy protocol with external cues was developed to improve gait was delivered post-surgery and was continued three times/week during 18-months. Physiotherapy sessions consisted of a personalized protocol of exercises with functional movements, balance, and gait training with external cues. Improvements in gait were observed in 3-months post-intervention and were more expressive in 6-months follow-up. Our patient improved substantially HD motor symptoms and her quality of life after GPi-DBS intervention and a physiotherapy program ICF-based. The objective outcomes measures used to assess gait have served as endpoints to assessing the patient's motor profile during the pre-operative period. Assessments were helpful to verify the efficacy of the multidisciplinary intervention in long-term. Conclusion: Periodically assessing function and disability using outcome improvements may support clinicians' decisions about DBS, medication adjustments and guide physiotherapists to personalize the ICF-based intervention.